Effect of saliva contamination on the shear bond strength of two types of glass- ionomer cements to dentin in primary teeth - Soleymani AA; Bahrololoomi Z; Namiranian P (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: Use of glass ionomer cements in pediatric dentistry is increasing and limited information exists with regard to the effect of salivary contamination on the shear bond strength of glass-ionomer to dentin in primary teeth. The aim of this study was to evaluate the effect of salivary contamination on the shear bond strength of two types of glass ionomer cements to dentin in primary teeth."nMaterials and Methods: A total of 36 human extracted primary molars were used in this study. The specimens were divided into two groups for each material and then further subdivided into three groups: group 1: uncontaminated, group 2: contaminated with saliva, group 3: contaminated, washed and air dried. The specimens in groups I, II, III were bonded to glass-ionomer and in groups IV, V, VI to resin modified glass-ionomer. Shear bond strength was measured using an Instron machine at 1 mm/min cross head speed. Data were analyzed with ANOVA and Tukey test."nResults: There were significant differences in the mean shear bond strength among groups IV, V (P=0.05). There were no significant difference among groups I & II (P=0.16), I & III (P= 0.93) and IV & VI (P=0.98)."nConclusion: Results showed that salivary contamination can decrease the mean shear bond strength of"nlight- cured glass-ionomer to dentin in primary teeth.